Redesain Pasar Kreneng Desa Dangin Puri, Kecamatan Denpasar Utara dengan Pendekatan Pasar Sehat: bahasa indonesia - I Gede Krisna Putra; Ni Wayan Meidayanti Mustika; Ni Luh Putu Indiani; I Wayan Widanan; Ni Komang Indra Mahayani (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Kreneng Market has been established since 1979. Based on observations, the current condition of Kreneng Market is not as good as previous conditions. There are several facilities that are poorly maintained and therefore look rundown and dirty, starting with several stalls with holes in the ceiling, poor lighting systems, poorly organized circulation patterns, and disorganized distribution and grouping between types of goods. Apart from that, there is also a lack of parking space; many public transport and cars carrying merchandise park their vehicles on the side of the road, which causes traffic jams. With this redesign, it is hoped that it will be able to provide and fulfill appropriate facilities for traders and visitors, such as loading and unloading areas, adequate parking facilities, health facilities, as well as grouping stalls or stalls of traders based on their trade. This research is qualitative descriptive research with data collection methods in the form of observation and literature study. The healthy market approach that will be planned will emphasize circulation aspects, interior layout arrangements, interior materials, and the use of furniture.